2018
DOI: 10.21608/edj.2018.78890
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD44 AND SOX-2 Cancer Stem cell Markers in The Development and Progression of Mucoepidermoid Carcinoma and Primary Squamous Cell Carcinoma of Salivary Glands

Abstract: One of the greatest difficulties to reach a successful treatment of mucoepidermoid carcinoma (MEC) and primary squamous cell carcinoma (PSSC) of salivary glands is the resistance to different therapeutic procedures which advocate the existence of a subpopulation of cancer stem cell (CSC). In salivary gland tumors the hypothesis of cancer stem cell has not been fully understood. Aim:To assess the expression of cancer stem cell markers CD44 and SOX2 in low and highgrades MEC and PSSC and to determine whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
(70 reference statements)
2
3
1
Order By: Relevance
“…Solely an association of lower SOX2 expression with higher histopathologic grade was found in MEC patients. Contrary to the present study, Kamal32 revealed higher level of SOX2 expression in high-grade MECs. According to Thierauf et al,33 lack of expression of SOX2 marker mainly occurs in solid and high-grade AdCCs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Solely an association of lower SOX2 expression with higher histopathologic grade was found in MEC patients. Contrary to the present study, Kamal32 revealed higher level of SOX2 expression in high-grade MECs. According to Thierauf et al,33 lack of expression of SOX2 marker mainly occurs in solid and high-grade AdCCs.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our findings, Kamal's study also showed that all MECs were positive for CD44. 32 This study indicated a trend toward high CD133 expression in AdCC patients with poor outcomes such as high histopathologic grade, positive recurrence, lymph node involvement, positive distant metastasis, and death caused by disease. MEC tumors manifested a reduction of this marker with the outcomes as mentioned earlier.…”
Section: High Expression Low Expressionmentioning
confidence: 61%
“…The lowest and highest grade MEC revealed a high mean value in high grade MEC, whereas the lowest mean was in low grade MEC, with a statistically significant difference. In agreement with our findings, it was reported that the highest mean value was recorded in MEC high grade, while the lowest value was recorded in MEC low grade, with a statistically significant difference (20) . In accordance with our findings CD44 was demonstrated in high grade MEC as compared to low grade MEC, which was significantly over-expressed, with significant correlation with proliferative activity and motility (19) .…”
Section: Discussionsupporting
confidence: 93%
“…In comparison to low-grade tumors, strong CD44 expression was already reported in high-grade MEC. Notably, the authors reported significant associations between CD44 expressions with recurrences/metastases (20) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation